Teacher Practices using Computer Assisted Instruction (CAI) with Technological Pedagogical Content Knowledge (TPACK) framework in English Classroom at Elementary School - Eril Sandi Sandi; Nurdin Noni; Muhalim (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This study was conducted to identify teacher practices in implementing Computer Assisted Instruction in English Language Learning in elementary school classes based on the TPACK framework and to explore EFL teachers' perception of using Computer Assisted Instruction learning models in elementary school classes. This study used a descriptive qualitative research method. English teachers in 2 private schools in Makassar, namely the first in SD Islam Athirah 2 Makassar and SD IT Darul Fikri Makassar, were selected as research subjects. Data were collected through observation and interviews. The result of this study indicated that (1) all teachers who were the study subjects used the CAI learning model with the explanation from Chan and Tsai (2005) that Computer-assisted learning is a learning method that uses technology. In this research, technology does not stand alone. Still, it is integrated with other aspects, and this combination is called the TPACK framework, which consists of three main elements and four meeting points. Shulman (1986) was the first person to develop the TPACK framework, which was later expanded by Mishra and Koehler (2006) by adding technology elements between them so that CAI learning models could be achieved well. (2) There are two main perspectives, namely, teachers assume that this learning method is very effective if applied in elementary schools but with some important notes such as teacher ability both in the form of providing student learning media to handling student activities in class and teacher understanding of using technology to support enjoyable learning. The teachers agree that this learning model makes students very happy in the learning process and makes it easy to understand the material to get high learning motivation. The researcher hopes that this research can contribute positively and benefit researchers, EFL teachers, students, and other fellow researchers.